Use of Flash Card Media in Early Childhood English Learning - Riska Nofianti, Farhati (International Proceedings of Nusantara Raya, 2023)
This study was conducted with the aim of introducing English vocabulary in early childhood using flash card media in private English class children. The subjects studied in this study were private English class children. The method used in this study is a descriptive qualitative method using data collection techniques in the form of observation, interviews and documentaries. The data analysis technique used in this study is content analysis from Miles and Huberman. The results obtained from this study are the use of flash card media in early childhood English learning in private English classes is quite effective to introduce children to English vocabulary. Through flash card media in which there are color images containing English vocabulary introduced to children.